Literasi Sains Anak Usia Dini Melalui Pembelajaran Proyek Menggunakan Loose Parts - Sakina; Hapidin; Nurani, Yuliani (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Science literacy in early childhood is essential for building scientific understanding and skills that will continue throughout life. This article discusses the use of project learning utilizing loose part media as an effective method to improve children's science literacy. Loose parts, which include a variety of natural and artificial materials that are flexible in their use, provide opportunities for children to be creative and explore science concepts directly. This study uses the Action Research method, this study involves teachers directly in improving classroom learning practices. This study was conducted at TK Aisyiyah Bustanul Athfal 27 Depok. Data collection techniques were carried out through triangulation (interviews, observation and documentation). The technique used is purposive sampling through project learning, children are involved in the process of identifying problems, planning, data collection, analysis, and presentation of results. This approach encourages critical thinking skills, collaboration, and increases curiosity and creativity. The resulting data is processed using the Miles & Huberman Interactive Model. The results of the implementation of this method show an increase in children's understanding of science concepts and practical skills. Thus, loose parts-based project learning has proven to be an effective means to support science literacy in early childhood.